Estudio de factibilidad económico social para la extracción de aceite de aguacate gourmet en la comunidad de Chaquibamba de Guayabamba y se distribuirá en los Restaurantes de la ciudad de Quito - Cueva Cabrera, Darwin Arturo (2014)
This proyectoestá oriented to strengthen the social economy community of Gullabamba Chaquibamba so they find new opportunities to industrialize their production of avocados and for this to be done a number of studies that could lead to identifying whether the project is viable . This project is aimed at extracting gourmet avocado oil before being distributed in gourmet restaurants in the city of Quito. Will use mechanical processes that do not harm the environment and help to obtain a high quality oil for extraction of avocado oil.